Endohelminth parasites in the native fish Galaxias maculatus (Jenyns, 1842) and Basilichthys australis Eigenmann, 1928 in Lake Pullinque, Chile - Torres, Patricio (2023)
The purpose of the study was to identify the endohelminths of the native fish Galaxias maculatus and Basilichthys australis in Lake Pullinque Chile, determine their prevalence, mean intensity, mean abundance, their zoonotic potential, describe new taxa for Chile, and evaluate the potential histopathological changes in parasitized samples of intestine of B. australis. Trematodes (Steganoderma szidati, Acanthostomoides apophalliformis, Tylodelphys sp, Posthodiplostomum sp) nematodes (Contracaecum sp, Camallanus corderoi and Eustrongylides sp) and the acanthocephalan Acanthocephalus tumescens was reported in G. maculatus. Tylodelphys sp presented the highest prevalence (97%) and mean abundance (21.1), while Posthodiplostomum sp showed the highest mean intensity (33.5). Trematodes (Limnoderetrema tolosai, Austrodiplostomum mordax and Tylodelphys destructor) and nematodes (Contracaecum sp, Hysterothylacium geschei and C. corderoi) were identified in B. australis. The highest prevalence (100%), mean intensity (71.9) and mean abundance (71.9) corresponded to L. tolosai. The histopathological study in B. australis showed adults of L. tolosai adhered to the surface of the intestinal mucosa, damaging the epithelium of the villi, and larvae of Contracaecum sp encapsulated and associated with mild congestion and few mononuclear cells in the connective tissue of the submucosa. All taxa were recorded for the first time in fish from Lake Pullinque. Eustrongylides sp and S. szidati were described for the first time in Chile being ustrongylides sp the only potentially zoonotic taxon.